Seven snail species hidden in one: Biogeographic diversity in an apparently widespread periwinkle in the Southern Ocean - Gonzalez-Wevar, Claudio A.; Segovia, Nicolas; Rosenfeld, Sebastian; Maturana, Claudia S.; Jeldres, Vanessa; Pinochet, Ramona; Saucede, Thomas; Morley, Simon A.; Brickle, Paul; Wilson, Nerida G.; Spencer, Hamish G.; Poulin, Elie (My University, 2022)
Aim The Antarctic Circumpolar Current imparts significant structure to the Southern Ocean biota. The Antarctic Polar Front is a major barrier to dispersal, with separate species (or sometimes intraspecific clades) normally occurring either side of this feature. We examined the biogeographic structure of an apparent exception to this rule in a widespread genus of the Southern Ocean, the periwinkle snail, Laevilitorina. Location Southern Ocean. Taxon Littorinidae, Laevilitorininae, Laevilitorina. Methods Using 750 specimens from 16 Southern Ocean Laevilitorina populations across >8000 km, we analysed mitochondrial COI and nuclear 28S sequences to uncover the evolutionary history of these marine near-shore snails. We utilized multi-locus phylogenetic reconstructions, species-delimitation analyses, divergence-time estimations and geometric morphometrics. Results Molecular data revealed that the widespread nominal species L. caliginosa comprises seven species-level clades, all supported by morphological data, whereas the Antarctic nominal species L. antarctica, L. claviformis and L. umbilicata are conspecific. Six "caliginosa" clades are restricted to southern South America, but one lineage extends from Antarctica to distant sub-Antarctic islands on both sides of the APF. Geometric morphometrics also identified significant differences among these clades, but uncoupled from genetic differentiation. Main conclusions The apparent trans-APF distribution of the poorly dispersing Laevilitorina caliginosa is largely illusory: this taxon consists of at least seven discrete species, only one of which has a trans-APF distribution. Similar to most Laevilitorina species, the remaining six "caliginosa" clades are narrow endemics. Biogeographical patterns in Laevilitorina reflect the role of vicariance associated with geological processes together with recent long-distance dispersal events. Laevilitorina originated near the Eocene/Oligocene boundary and diversified during the Miocene and the Pliocene. Laevilitorina is not a cryptic-species complex: speciation was accompanied by hitherto unrecognized morphological differentiation. This study represents the most detailed molecular work on Southern-Ocean littorinids and reveals unforeseen diversity across this globally important region.
Keywords: antarctic; cryptic species; dispersal; littorinidae; species-delimitation analyses; sub-antarctic; vicariance